MEN’S KNITTED CLOTHING IN ANIMAL STYLE - DZYKOVYCH, TETIANA; VORONA, IRYNA; PUSTOVOJT, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The purpose of the work is to design an author’s collection of men’s knitwear in an animalistic style. To achieve the goal, the fashion trends of knitted men’s clothing of modern collections of famous designers and the assortment of men’s products for everyday wear were studied. A survey of literary sources on the issues of research on the development of the style and assortment of men’s clothing was conducted. An analysis and study of the use of animalistic style in clothing was carried out based on current fashion and collections of past years. Clothing in the animalistic style was separated and researched in three directions, namely: artistic design of clothing with ornaments in the form of stylized drawings of the color of the skin or fur of animals, compositional design of clothing with visual ornaments in the form of reports of stylized animals, and costume format clothing in the form of a stylized image of animals. In the course of research, tables of the use of animalistic ornaments, color gamut in the collections of famous designers were developed and corresponding diagrams were constructed.  As a result of the work, a sketch project of a collection of men’s knitted clothes in an animalistic style was developed. The author’s report of the ornament was designed by means of artistic stylization and transformation of the pattern based on the selected primary source, namely the color of the python skin, and the program of the pattern cartridge for knitting the collection was developed. For knitting the products, a weave was chosen – knitwear of double incomplete jacquard weave, and an industrial sample was made for introduction into production.
Keywords: clothing style; animalistic style; knitwear; men’s clothing; structure of a two-colour Jacquard ‘stitch